Investment analytic / Muhammad Shamil Samsul Kamal ... [et al.] - Samsul Kamal, Muhammad Shamil; Tengku Hilmi Suleman, Tengku Abdul Samad Shah; Md Zamri, Muhammad Shazani Zamir; Rosli, Nur Hana Qistina; Husain, Nuratikah (2019)
The study on microeconomic as well as macroeconomics which will be narrowed down to the study of those factors that would affect the performance of economics of country . To identify the trends of economic performance base on four factors (Inflation rate , Unemployment rate , Gross domestic product rate and Interest rate) for 3 years . With these studies we will conclude our analyses in expected future economic conditions. The study will be conducted by comparing domestic economy (Malaysia) between World Economy(Great Britain , Japan , South Korea , France and Saudi Arabia) and Regional Economy (Laos , Thailand Philippines , Laos , Brunei and Singapore) base on 4 factors ( Inflation rate , Unemployment rate , Interest rate and GDP)